Main Drivers of Economic Growth in Armenia: Analysis and Evaluation - E. M. Sandoyana; A. A. ghiazaryan; M. A. Voskanyan; A. G. Galstyan (Финансы: теория и практика, 2022)
Macroeconomic policy in Armenia over the past 30 years has led to a slowdown in economic growth. This, in turn, entails the need to revise approaches to macroeconomic regulation, as well as to search for key drivers of economic growth, which the state should emphasize in the future macroeconomic policy. The aim of this research is to analyze and assess the main drivers of economic growth in Armenia. We have employed the methods of statistical and comparative analysis, deductive analysis, as well as the analysis of historical data and the current state of the problem. The paper examines the key drivers of economic growth in Armenia, as well as periods of both a stable macroeconomic environment and economic crises, from the point of view of the efficiency and optimality of macroeconomic regulation. The current study identifies the most important sectors of the economy, analyses macroeconomic policy regulation in Armenia, and assesses the impact of such policies on economic growth in the country. The results show that today’s macroeconomic regulation can be considered ineffective, which certainly has a negative effect on the rate of economic growth. The key conclusion of the research is the thesis that it is urgent to develop new socio-economic policy approaches to ensure sustainable economic growth in the future and to emerge quickly from future economic growth crises without restricting or halting economic activity.